(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Business Communication Skills is a text book published in 2013 by Maria Esther Rodriguez Gil and Daniela Cecic as authors. The book was envisioned to be used in Business related subjects and as a self- study book. The book offers 6 chapters about Business English: application forms, e-mails, negotiations, CV and cover letter and presentations. It contains readings, exercises and keys. Each chapter has an original reading text adapted for the B1- B2 level purposes. In 2018 it was decided to change and update the information due to some feedback received by the readers. Instead of application forms, we are going to introduce how to make a video CVs and one subchapter related to the use of social media such as LinkedIn in order to find a job. The changes are in process and will be presented at this conference for the first time. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.